Training Tomorrow' Military Surgeons: Lessons from the Past and Challenges for the Future. Issue 4 (1st December 2009) - Eardley, WGP; Taylor, DM; Parker, PJ
Abstract : The nature of conflict is evolving, with current warfare being associated with an initial "shock and awe" phase followed by protracted periods of counter-insurgency and peace support missions. As conflict has changed, so have the munitions deployed and the resulting patterns of injury. Improvised Explosive Devices have become the preferred weapon of the insurgent and the resultant explosive and fragmentation injuries are the hallmark of modern military wounding. These injuries pose a significant challenge to deployed medical forces, requiring a well-defined, seamless approach from injury to rehabilitation. Traditionally, military medical services demonstrate a poor 'institutional memory' in the maintenance of combat surgical skills. Numerous publications detail the re-learning of key tenets of war surgery by generations of surgeons deploying onto the field of battle. While the maintenance of military surgical capability in trained surgeons may be addressed through combat surgical courses, concern exists as to the generic competency of those currently in training and their ability to deal with the burden of injury associated with modern conflict. The training of junior doctors in the United Kingdom and further afield is in a state of flux. New curriculum development, streamlined and run-through training programmes have combined with the legal requirements of the European Working Time Directive to produce a training landscape almost unrecognisable with that of previous years. This article investigates the development of current military wounding patterns and modern surgical training programmes. It describes processes already in place to address the unique training needs of military surgeons and proposes a framework for enabling appropriate training opportunities in the future.